Effectiveness factors for a partially wetted catalyst based on the rivulet flow model. (6th April 2020) - Tang, Yanling; Chen, Meichen; Cheng, Zhenmin; Yang, Tao; Chen, Bo; Ge, Hailong; Fang, Xiangchen
Highlights: Experiments were conducted to identify the wetting morphology over a particle. Effectiveness factors were calculated by using finite element method. The difference between rivulet and film flow models can be ignored when f > 0 . 4 . Thiele modulus can be modified as ϕ / f for liquid-limited reactions. Abstract: Partial wetting is a common phenomenon in a trickle bed reactor, which causes nonuniform mass transfer flux at the external surface of the catalyst. Previous work on effectiveness factor for a partially wetted catalyst are mainly based on the assumption that the spherical catalyst is wetted by a liquid film. In fact, it is only true when the liquid-solid contact angle is very small. In most situations, rivulet flow prevails. The purpose of the article is to calculate effectiveness factors for both gas-limited and liquid-limited reactions under the two wetting modes by using finite element method (FEM). The effects of wetting efficiency, Biot number, and Thiele modulus on effectiveness factors are investigated. On the basis of the FEM results, the intrinsic reason for the variation of effectiveness factors with respect to wetting efficiency is revealed, and good agreements are observed between this work and the conventional models.